A route to a high-impact journal article: The most functional strategy in modern history - Wan Sharuzi, Wan Harun; Kumaran, Kadirgama; Devarajan, R.; Norazlianie, Sazali (Penerbit UMPSA, 2023)
This book contains valuable information for readers seeking to make informed decisions. However, it is crucial to seek the advice of professionals (such as legal or financial advisors) before making any decisions based on the content of this book. The book also features information, products or services from third-party sources, and we do not assume responsibility or liability for their accuracy or opinions. Conducting due diligence and independently verifying all information, products and services before making any business decisions are essential.The book also features information, products or services from third-party sources, and we do not assume responsibility or liability for their accuracy or opinions. Conducting due diligence and independently verifying all information, products and services before making any business decisions are essential.